2014
DOI: 10.3109/0886022x.2014.970469
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transdermal insulin treatment of streptozotocin-induced diabetic rats on kidney function and renal expression of glucose transporters

Abstract: The tight glycemic control required to attenuate chronic complications in type 1 diabetes mellitus requires multiple daily injections of bolus insulin which cause hyperinsulinemic edema and hypertension due to Na + retention. Reports indicate that pectin insulin (PI)-containing dermal patches sustain controlled insulin release into the bloodstream of streptozotocin (STZ)-induced diabetic rats. This study investigated whether PI dermal patches can improve the impaired renal function in diabetes. PI patches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…This data demonstrates the ability of the OA-pectin patch to deliver sustained controlled therapeutic doses of OA which reduced and cleared the malaria parasites within a period of 4 days. Indeed, we have previously reported on the ability of transdermal systems to deliver drugs in a sustained controlled manner [2330]. Similar to CHQ, both transdermal and orally administered OA were able to reduce parasitaemia to undetectable levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data demonstrates the ability of the OA-pectin patch to deliver sustained controlled therapeutic doses of OA which reduced and cleared the malaria parasites within a period of 4 days. Indeed, we have previously reported on the ability of transdermal systems to deliver drugs in a sustained controlled manner [2330]. Similar to CHQ, both transdermal and orally administered OA were able to reduce parasitaemia to undetectable levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that these triterpenes are of low solubility when administered orally, which ultimately affects their bioavailability [2021]. We have reported on the ability of transdermal CHQ and insulin matrix-pectin patch to provide sustained controlled release of CHQ and insulin over a period of time, respectively [2224]. Against this background, the current study evaluated the effects of transdermally delivered OA and CHQ-OA combination on P .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies for GLUT1 evaluation in these models were carried out in streptozotocin (STZ) rats. They predominantly reported higher GLUT1 protein [79][80][81][82] and corresponding mRNA [81][82][83][84][85] contents in the whole kidney and increased GLUT1 protein [86,87] and mRNA [86,88,89] in the cortex. Nonetheless, these studies are yet controversial [22,67,[90][91][92][93].…”
Section: Tubular Glucose Transporters In Animal Models Ofmentioning
confidence: 99%
“…Non-diabetic animals served as the absolute control. Two days prior to the application of the pectin-insulin patches, the rats were shaved on the dorsal region of the neck [14]. The pectin-insulin patches were applied thrice daily, 8 hours apart for 5 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we have successfully developed a transdermal pectin-insulin patch formulation that can deliver physiologically relevant insulin concentration which can maintain normal glycaemic control and ameliorate certain diabetes associated complications in streptozotocin (STZ) induced-diabetic rats [13, 14]. Accordingly, in the study, we sought to evaluate the effects of transdermal pectin-insulin patch application on markers of kidney function such as blood pressure, creatinine clearance, albumin excretion rate, kidney nephrin expression and urinary nephrin concentration.…”
Section: Introductionmentioning
confidence: 99%